Jurassic to Paleogene magmatic evolution of the Southern Central Andes (36–42º S) triggered by changes in tectonic style - Omar Sebastian Assis; Natalia Hauser; Claudia Beatriz Zaffarana; Darío Orts; Sebastián Pernich; Gloria Gallastegui; Wolf Uwe Reimold; Cristiano Lana (Journal of Geodynamics, 2026)

Hirudins and ornatins in five species of the genus Placobdella (Annelida: Hirudinea: Glossiphoniidae) - Raja Ben Ahmed; Robert Wolf; Gabriele Jedlitschky; Céline Tolksdorf; Bernhard H. Rauch; Clemens Grosser; Sebastian Kvist; Christian Müller (Protoplasma, 2026)
Leeches of the genus Placobdella Blanchard, 1893 (Annelida: Rhynchobdellida: Glossiphoniidae) are mainly distributed across North and Central America, but at least two species are also present in the palearctic region: the European turtle leech Placobdella costata Müller, 1846, and the North African turtle leech Placobdella nabeulensis Ben Ahmed et al., 2023. All species of the genus are hematophagous and feed on vertebrates, but are known to preferentially target aquatic and semi-aquatic reptiles like turtles and snakes. Placobdella ornata Verrill, 1872, is the original source of ornatins, a class of potent platelet aggregation inhibitors. However, the whole repertoire of bioactive peptides, including anticoagulation factors remains largely underexplored for Placobdella , and functional characterizations of putative antithrombotics are scarce. Here we describe the genes and cDNAs that encode putative hirudins and ornatins in both of the palearctic and three American species of the genus Placobdella . A selection of putative hirudins and ornatins was recombinantly expressed and functionally characterized using appropriate coagulation and platelet aggregation assays, and our data confirm the expression of functional hirudins and ornatins in the studied leeches. In addition, our genetic analyses strongly support the hypothesis that blood feeding evolved only once in the evolutionary history of leeches.

A new oxidative pathway of nitric oxide production from oximes in plants - Pedro López-Gómez; Javier Buezo; Marina Urra; Alfonso Cornejo; Raquel Esteban; Jorge Fernández de los Reyes; Estibaliz Urarte; Estefanía Rodríguez-Dobreva; Alejandro Chamizo-Ampudia; Alejandro Eguaras; Sebastian Wolf; Daniel Marino; et al. (Molecular Plant, 2026)

“mentalFIT”: a pilot, randomized controlled trial investigating cognitively engaging exercise for executive functions - Britta Seiffer; Sebastian Wolf (German Journal of Exercise and Sport Research, 2026)
Objective This randomized-controlled pilot trial assesses the effects of a 6-week cognitively engaging exercise intervention (CE-EX) vs. repetitive endurance exercise (R-EX), and a control group (CTRL), before (pre), after (post) the intervention and at a 3-month follow-up, for executive functions (EF) in a sample of young adults ( N = 46, m age = 23.76 ± 3.26 years). Methods We performed a linear mixed model with the timepoint × group interaction and participant (ID) as random effect and EF as outcome. Since the completion rate of the intervention was low (CE-EX: 58.33%, R‑EX: 36.26%), we further performed a sensitivity analysis differentiating between those who received the intended dose (completers) of the intervention and those who did not (noncompleters). Results In the primary analysis, we did not find a significant interaction effect. In the sensitivity analysis, the linear mixed model resulted in significant interaction effect of timepoint × group × intervention-completion (Chi 2 (2) = 15.16, p = 0.001). In the post hoc tests, due to Bonferroni correction and a small sample size, there was no significant difference within or between groups in the post hoc tests. Regarding our main hypothesis of changes in EF between groups, we descriptively report a larger change towards better EF for CE-EX completers from pre- to postassessment than in R‑EX completers with small to moderate effects (| d | = 0.37). Conclusion Our results imply that intervention adherence plays a crucial role to obtain the desired positive intervention effects of exercise-inherent cognitive engagement for EF. These results should be verified in a larger study, which focuses on improving intervention adherence.

Influence of surgical intervention on pre- and post-surgery patient specific muscle synergies in children with cerebral palsy - Tiana Breust; Jiayin Lin; Vincent C. K. Cheung; Firooz Salami; Sebastian I. Wolf; Gursel Alici; Manish Sreenivasa (Experimental Brain Research, 2026)
Muscle synergy analysis has been explored as means to better understand changes in motor control, with the aim to improve treatment outcomes after Single Event Multilevel Surgery (SEMLS) for children with cerebral palsy (CP). In this single-group study, we assess changes between pre- and post-surgery muscle synergies at both patient specific, and cohort levels after surgical intervention for children with CP. We analysed the walking data of 11 patients between the ages of 7–18 years old, including surface electromyography, joint angles and ground reaction forces, recorded before and after surgery. Muscle synergies were extracted and assessed for changes in dimensionality and sparseness between pre- and post-surgery. Our results show that at a patient specific level, pre- and post-surgery muscle synergies were not highly similar, with only 41% of paired synergies showing high correlation ( $$r$$ $$>$$ 0.8) after surgery, and an overall mean correlation of 0.53 $$±$$ 0.25. On the other hand, synergies obtained at the cohort level were highly similar post-surgery ( $$r$$ $$>$$ 0.87). These findings suggest that at an individual level, pre-surgery motor control cannot be assumed to be preserved post-surgery. CP synergies obtained at the cohort level from pre-surgery data can demonstrate more reliable preservation in post-surgery motor control. We also observed sparseness increasing with the number of synergies, which provides an interesting future research direction exploring the link with more complex motor control and a more typical gait pattern.

Comparison of deep and conventional machine learning methods in predicting joint moments in patients with cerebral palsy - Mustafa Erkam Özates; Firooz Salami; Sebastian Immanuel Wolf; Yunus Ziya Arslan (Medical & Biological Engineering & Computing, 2026)

Flux Footprints: A Critical Link to Bridge Eddy‐Covariance Measurements With Models, Remote Sensing, and Other Observations - Housen Chu; Stefan Metzger; Zutao Ouyang; Anne Griebel; Koong Yi; David Durden; Sebastian Wolf; Kuno Kasak; Camilo Rey‐Sanchez; Leila Constanza Hernandez Rodriguez; Patty Oikawa; Nicola Falco; et al. (Global Change Biology, 2026)
Global networks of eddy‐covariance flux towers play a pivotal role in enhancing our predictive understanding of carbon and water cycling of biological systems in response to regional and global environmental change. Despite their broad application in numerous studies, the spatial aspects of the flux measurements have often been ignored or treated ambiguously, thereby remaining a primary source of uncertainty. The area contributing to the flux—referred to as the flux footprint—varies over time depending on wind direction, atmospheric turbulence, effective measurement heights, surface characteristics, and mesoscale forcings. The footprint dynamics, along with underlying source‐sink heterogeneity, lead to spatial and temporal variability in the sensed fluxes, complicating the interpretation of flux data and their integration with a range of observations and models. This article addresses this critical link by reviewing the most up‐to‐date research, identifying knowledge gaps and challenges, and pointing out future research needs and opportunities. We begin with an overview of the current state of footprint modeling and its applications, from single‐site studies to large‐scale syntheses, summarizing how flux footprints have been used to interpret spatial flux variability and to integrate flux data with models, remote sensing, and other observations. We highlight how this critical spatial aspect could complicate the processing of eddy‐covariance fluxes, the definition of mass and energy continuity, and the interpretation of flux response functions and parameters, all of which have significant implications for numerous applications and research. We then point out potential opportunities and future research needs to bridge this knowledge gap, highlighting both readily available and prominent emerging ones. We conclude by urging the scientific community to (re)consider the spatiotemporal dynamics of eddy‐covariance flux measurements, and to investigate and evaluate potential approaches across scales, applications, and disciplines.

Exercise therapy innovations in outpatient mental health care - David Victor Fiedler; Stephanie Rosenstiel; Stefan Peters; Anna Lena Flagmeier; Lena Zwanzleitner; Leonie Sundmacher; Ander Ramos-Murguialday; Martin Hautzinger; Thomas Ehring; Sebastian Wolf; Gorden Sudeck (German Journal of Exercise and Sport Research, 2025)
For successful implementation of healthcare interventions, attitudes of healthcare professionals are a key factor. Research in the field of psychological treatment suggests that attitude towards evidence-based practice (EBP) may play a crucial role. However, little research has been conducted on the extent to which this applies to the field of exercise therapy, where there is a strong need for development regarding the dissemination of EBP. A recent pragmatic multisite randomized controlled trial (ImPuls) can serve as an innovative example for the implementation of an evidence-based exercise intervention including behavior change techniques within the outpatient mental health care system in Germany. The aim of the current study was to explore the role of exercise therapists’ attitude towards EBP for an implementation process by identifying relationships with other factors of importance for implementing innovations (e.g., motivation or self-efficacy). Exercise therapists ( n = 26) completed online surveys pre- (week 0) and postintervention (week 24+). Correlation analyses and linear regressions were performed considering a total score for attitude towards EBP as well as mean scores for its subdimensions. The total score was rather positive (mean = 2.58, standard deviation = 0.43) and significantly related to program-specific motivation ( r = 0.64, p < 0.001), self-efficacy ( r = 0.42, p < 0.034), and acceptance ( r = 0.56, p < 0.003) at baseline. Exercise therapists’ education and further training should therefore have an increased focus on EBP, including the usage of scientific findings, the integration into routine practice and the scopes and obligations that come along with it.

POLARIS: The POLArized RadIation Simulator for Mie scattering in optically thick dusty plasmas - Julia Kobus; Stefan Reißl; Moritz Lietzow-Sinjen; Alexander Bensberg; Andreas Petersen; Franko Greiner; Sebastian Wolf (Computer Physics Communications, 2025)

Estimating Ground Reaction Forces from Gait Kinematics in Cerebral Palsy: A Convolutional Neural Network Approach - Mustafa Erkam Ozates; Firooz Salami; Sebastian Immanuel Wolf; Yunus Ziya Arslan (Annals of Biomedical Engineering, 2025)

Corrigendum to “Does experience matter? Assessing user motivations to accept a vehicle-to-grid charging tariff” [Transp. Res. D 113 (2022) 103528] - Nora Baumgartner; Franziska Kellerer; Manuel Ruppert; Sebastian Hirsch; Stefan Mang; Wolf Fichtner (Transportation Research Part D: Transport and Environment, 2025)

Similarities in the Electrographic Patterns of Delayed Cerebral Infarction and Brain Death After Aneurysmal and Traumatic Subarachnoid Hemorrhage - Jens P. Dreier; Coline L. Lemale; Viktor Horst; Sebastian Major; Vasilis Kola; Karl Schoknecht; Michael Scheel; Jed A. Hartings; Peter Vajkoczy; Stefan Wolf; Johannes Woitzik; Nils Hecht (Translational Stroke Research, 2025)
While subarachnoid hemorrhage is the second most common hemorrhagic stroke in epidemiologic studies, the recent DISCHARGE-1 trial has shown that in reality, three-quarters of focal brain damage after subarachnoid hemorrhage is ischemic. Two-fifths of these ischemic infarctions occur early and three-fifths are delayed. The vast majority are cortical infarcts whose pathomorphology corresponds to anemic infarcts. Therefore, we propose in this review that subarachnoid hemorrhage as an ischemic-hemorrhagic stroke is rather a third, separate entity in addition to purely ischemic or hemorrhagic strokes. Cumulative focal brain damage, determined by neuroimaging after the first 2 weeks, is the strongest known predictor of patient outcome half a year after the initial hemorrhage. Because of the unique ability to implant neuromonitoring probes at the brain surface before stroke onset and to perform longitudinal MRI scans before and after stroke, delayed cerebral ischemia is currently the stroke variant in humans whose pathophysiological details are by far the best characterized. Optoelectrodes located directly over newly developing delayed infarcts have shown that, as mechanistic correlates of infarct development, spreading depolarizations trigger (1) spreading ischemia, (2) severe hypoxia, (3) persistent activity depression, and (4) transition from clustered spreading depolarizations to a negative ultraslow potential. Furthermore, traumatic brain injury and subarachnoid hemorrhage are the second and third most common etiologies of brain death during continued systemic circulation. Here, we use examples to illustrate that although the pathophysiological cascades associated with brain death are global, they closely resemble the local cascades associated with the development of delayed cerebral infarcts.

Lysozyme: an endogenous antimicrobial protein with potent activity against extracellular, but not intracellular Mycobacterium tuberculosis - Felix Immanuel Maier; David Klinger; Mark Grieshober; Reiner Noschka; Armando Rodriguez; Sebastian Wiese; Wolf-Georg Forssmann; Ludger Ständker; Steffen Stenger (Medical Microbiology and Immunology, 2024)
Endogenous antimicrobial peptides (AMPs) play a key role in the host defense against pathogens. AMPs attack pathogens preferentially at the site of entry to prevent invasive infection. Mycobacterium tuberculosis ( Mtb ) enters its host via the airways. AMPs released into the airways are therefore likely candidates to contribute to the clearance of Mtb immediately after infection. Since lysozyme is detectable in airway secretions, we evaluated its antimicrobial activity against Mtb . We demonstrate that lysozyme inhibits the growth of extracellular Mtb , including isoniazid-resistant strains. Lysozyme also inhibited the growth of non-tuberculous mycobacteria. Even though lysozyme entered Mtb -infected human macrophages and co-localized with the pathogen we did not observe antimicrobial activity. This observation was unlikely related to the large size of lysozyme (14.74 kDa) because a smaller lysozyme-derived peptide also co-localized with Mtb without affecting the viability. To evaluate whether the activity of lysozyme against extracellular Mtb could be relevant in vivo, we incubated Mtb with fractions of human serum and screened for antimicrobial activity. After several rounds of sub-fractionation, we identified a highly active fraction-component as lysozyme by mass spectrometry. In summary, our results identify lysozyme as an antimycobacterial protein that is detectable as an active compound in human serum. Our results demonstrate that the activity of AMPs against extracellular bacilli does not predict efficacy against intracellular pathogens despite co-localization within the macrophage. Ongoing experiments are designed to unravel peptide modifications that occur in the intracellular space and interfere with the deleterious activity of lysozyme in the extracellular environment.

The ExoMars 2028 WISDOM antenna assembly: Description and characterization - Wolf-Stefan Benedix; Sebastian Hegler; Christoph Statz; Ronny Hahnel; Dirk Plettemeier; Valérie Ciarletti (Planetary and Space Science, 2024)

Development and operation of a novel non-invasive opto-acoustic underwater fish observatory in Kiel Bight, Southwestern Baltic Sea - Joachim P. Gröger; Boris Cisewski; Sabah Badri-Hoeher; Gordon Böer; Karin Boos; Catriona Clemmesen; Ala Cojocaru; Verena Dauben; Peter A. Hoeher; Andreas Lehmann; Sebastian Matz; Hela Mehrtens; et al. (Frontiers in Marine Science, 2024)
This study presents a trilateral test array of new opto-acoustic Underwater Fish Observatories (UFOs) that were operated and tested in Kiel Bight as part of the “UFOTriNet” project. While hydroacoustic and optical techniques have so far been used individually to observe and monitor fish stocks, we present a coupled hybrid system consisting of an optical device intended to scan the near-field as a subsample of a spatially larger medium-to-far-field, scanned by an acoustical device. The optical device consists of two residual light amplifying camera modules able to detect and classify various marine species at a high resolution in the range of at max 4 meters in the study area. To compensate for this spatial limitation, the acoustical component consists of a 2D imaging sonar with a maximum range of 50 m, albeit with a lower resolution. Species affiliation, morphometric characteristics of fish and other marine organisms were stereo-optically detected and classified in the nearfield, blended with acoustical activity in medium to far range, and projected onto the entire insonified area using a hybrid algorithm. Through the synchronous acquisition of multiparametric abiotic and biotic data, UFO allows an automatic, continuous, and non-invasive long-term monitoring of various fish and other marine species and their habitats at regional hotspots. An 86-day multiparametric sample revealing an abrupt shift from a clupeid fish to a gelatinous plankton dominated regime in summer/autumn 2021 in Kiel Fjord is used to demonstrate the potential of UFO for various applications.

Dynamics of evapotranspiration from concurrent above- and below-canopy flux measurements in a montane Sierra Nevada forest - Sebastian Wolf; Eugénie Paul-Limoges; Dan Sayler; James W. Kirchner (Agricultural and Forest Meteorology, 2024)

A new oxidative pathway of nitric oxide production from oximes in plants - Pedro López-Gómez; Javier Buezo; Marina Urra; Alfonso Cornejo; Raquel Esteban; Jorge Fernández de los Reyes; Estibaliz Urarte; Estefanía Rodríguez-Dobreva; Alejandro Chamizo-Ampudia; Alejandro Eguaras; Sebastian Wolf; Daniel Marino; et al. (Molecular Plant, 2024)

Low accuracy bark gouging controls Ips typographus outbreaks while conserving non-target beetle diversity - Sebastian Zarges; Simon Thorn; Heinz Bußler; Harald Siegler; Josef Wolf; Jonas Hagge (Forest Ecology and Management, 2023)

Cross-well multilevel pumping tests – A novel approach for characterizing the changes of hydraulic properties during gas storage in shallow aquifers - Linwei Hu; Maike Schnackenberg; Götz Hornbruch; Klas Lüders; Wolf Tilmann Pfeiffer; Ulrike Werban; Sebastian Bauer (Journal of Hydrology, 2023)

Prevalence of higher-grade dysplasia in persistently high-risk human papillomavirus positive, cytology negative women after introduction of the new cervical cancer screening in Germany - Laura Berger; Maja Wolf-Breitinger; Christel Weiß; Benjamin Tuschy; Sebastian Berlit; Marc Sütterlin; Saskia Spaich (Cancer Causes & Control, 2023)
Purpose According to the recently implemented organized cervical cancer screening program in Germany, women older than 35 years with negative cytology but persistent high-risk human papilloma virus (hrHPV) infection > 12 months should be referred to colposcopy for further evaluation. This study aimed to present and dissect colposcopic and histopathological findings with particular focus on associated hrHPV genotypes. Methods This study is a retrospective analysis of clinical data from 89 hrHPV positive patients with normal cytology who underwent colposcopic examination at a certified dysplasia outpatient clinic in Germany in 2021. Results While 38 (43%) women had a normal colposcopic finding, 45 (51%) had minor and 6 (7%) major changes. Thirty-one (35%) of the women were HPV 16 and/or HPV 18 positive and 58 (65%) women were positive for other hrHPV only. Among patients who underwent colposcopy with biopsies (in case of an abnormal finding or type 3 transformation zone, n = 68), eight (12%) had cervical intraepithelial neoplasia (CIN) 3 and six (9%) had CIN 2. The proportion of women diagnosed with CIN 3 varied among different hrHPV genotypes (HPV 16: 11%, HPV 18: 33%, HPV 31: 27%, HPV 33: 33%, HPV 52: 33%). Conclusion Persistently hrHPV positive women with negative cytology are at increased risk of being diagnosed with CIN 3. As CIN 3 prevalence seems to differ with regard to hrHPV strain, immediate HPV genotyping for risk stratification and subsequent early referral for colposcopy might constitute a feasible strategy.

Carbon farming: Are soil carbon certificates a suitable tool for climate change mitigation? - Carsten Paul; Bartosz Bartkowski; Cenk Dönmez; Axel Don; Stefanie Mayer; Markus Steffens; Sebastian Weigl; Martin Wiesmeier; André Wolf; Katharina Helming (Journal of Environmental Management, 2023)

The effect of relative humidity on eddy covariance latent heat flux measurements and its implication for partitioning into transpiration and evaporation - Weijie Zhang; Martin Jung; Mirco Migliavacca; Rafael Poyatos; Diego G. Miralles; Tarek S. El-Madany; Marta Galvagno; Arnaud Carrara; Nicola Arriga; Andreas Ibrom; Ivan Mammarella; Dario Papale; et al. (Agricultural and Forest Meteorology, 2023)

Pelagic and ice‐associated microalgae under elevated light and pCO 2 : Contrasting physiological strategies in two Arctic diatoms - Klara K. E. Wolf; Sebastian D. Rokitta; Clara J. M. Hoppe; Björn Rost (Limnology and Oceanography, 2022)
Sea ice retreat, changing stratification, and ocean acidification are fundamentally changing the light availability and physico‐chemical conditions for primary producers in the Arctic Ocean. However, detailed studies on ecophysiological strategies and performance of key species in the pelagic and ice‐associated habitat remain scarce. Therefore, we investigated the acclimated responses of the diatoms Thalassiosira hyalina and Melosira arctica toward elevated irradiance and CO 2 partial pressures (pCO 2 ). Next to growth, elemental composition, and biomass production, we assessed detailed photophysiological responses through fluorometry and gas‐flux measurements, including respiration and carbon acquisition. In the pelagic T. hyalina , growth rates remained high in all treatments and biomass production increased strongly with light. Even under low irradiances cells maintained a high‐light acclimated state, allowing them to opportunistically utilize high irradiances by means of a highly plastic photosynthetic machinery and carbon uptake. The ice‐associated M. arctica proved to be less plastic and more specialized on low‐light. Its acclimation to high irradiances was characterized by minimizing photon harvest and photosynthetic efficiency, which led to lowered growth. Comparably low growth rates and strong silification advocate a strategy of persistence rather than of fast proliferation, which is also in line with the observed formation of resting stages under low‐light conditions. In both species, responses to elevated pCO 2 were comparably minor. Although both diatom species persisted under the applied conditions, their competitive abilities and strategies differ strongly. With the anticipated extension of Arctic pelagic habitats, flexible high‐light specialists like T. hyalina seem to face a brighter future .

Novel aspects of age-protection by spermidine supplementation are associated with preserved telomere length - Alexander Wirth; Bettina Wolf; Cheng-Kai Huang; Silke Glage; Sebastian J. Hofer; Marion Bankstahl; Christian Bär; Thomas Thum; Kai G. Kahl; Stephan J. Sigrist; Frank Madeo; Jens P. Bankstahl; et al. (GeroScience, 2021)
Ageing provokes a plethora of molecular, cellular and physiological deteriorations, including heart failure, neurodegeneration, metabolic maladaptation, telomere attrition and hair loss. Interestingly, on the molecular level, the capacity to induce autophagy, a cellular recycling and cleaning process, declines with age across a large spectrum of model organisms and is thought to be responsible for a subset of age-induced changes. Here, we show that a 6-month administration of the natural autophagy inducer spermidine in the drinking water to aged mice is sufficient to significantly attenuate distinct age-associated phenotypes. These include modulation of brain glucose metabolism, suppression of distinct cardiac inflammation parameters, decreased number of pathological sights in kidney and liver and decrease of age-induced hair loss. Interestingly, spermidine-mediated age protection was associated with decreased telomere attrition, arguing in favour of a novel cellular mechanism behind the anti-ageing effects of spermidine administration.

Ecosystem transpiration and evaporation: Insights from three water flux partitioning methods across FLUXNET sites - Jacob A. Nelson; Oscar Pérez‐Priego; Sha Zhou; Rafael Poyatos; Yao Zhang; Peter D. Blanken; Teresa E. Gimeno; Georg Wohlfahrt; Ankur R. Desai; Beniamino Gioli; Jean‐Marc Limousin; Damien Bonal; et al. (Global Change Biology, 2020)
We apply and compare three widely applicable methods for estimating ecosystem transpiration ( T ) from eddy covariance (EC) data across 251 FLUXNET sites globally. All three methods are based on the coupled water and carbon relationship, but they differ in assumptions and parameterizations. Intercomparison of the three daily T estimates shows high correlation among methods ( R between .89 and .94), but a spread in magnitudes of T /ET (evapotranspiration) from 45% to 77%. When compared at six sites with concurrent EC and sap flow measurements, all three EC‐based T estimates show higher correlation to sap flow‐based T than EC‐based ET. The partitioning methods show expected tendencies of T /ET increasing with dryness (vapor pressure deficit and days since rain) and with leaf area index (LAI). Analysis of 140 sites with high‐quality estimates for at least two continuous years shows that T /ET variability was 1.6 times higher across sites than across years. Spatial variability of T /ET was primarily driven by vegetation and soil characteristics (e.g., crop or grass designation, minimum annual LAI, soil coarse fragment volume) rather than climatic variables such as mean/standard deviation of temperature or precipitation. Overall, T and T /ET patterns are plausible and qualitatively consistent among the different water flux partitioning methods implying a significant advance made for estimating and understanding T globally, while the magnitudes remain uncertain. Our results represent the first extensive EC data‐based estimates of ecosystem T permitting a data‐driven perspective on the role of plants’ water use for global water and carbon cycling in a changing climate.

Porcine models for studying complications and organ crosstalk in diabetes mellitus - Simone Renner; Andreas Blutke; Sebastian Clauss; Cornelia A. Deeg; Elisabeth Kemter; Daphne Merkus; Rüdiger Wanke; Eckhard Wolf (Cell and Tissue Research, 2020)

Journal Club - Fabian M. Commichau; Jannis Anstatt; Sven Krappmann; Evi Stegmann; Sebastian Banhart; Kai Papenfort; Sascha Brunke; Bernhard Hube; Marc Bramkamp; Miriam Herbert; Johannes Sander; Jonathan Wolf Mueller; et al. (BIOspektrum, 2020)

Journal Club - Sandra Wiegand; Daniela Kruck; Sebastian Lücker; Johannes Sander; Jonathan Wolf Mueller (BIOspektrum, 2019)

Covariations between plant functional traits emerge from constraining parameterization of a terrestrial biosphere model - Marc Peaucelle; Cédric Bacour; Philippe Ciais; Nicolas Vuichard; Sylvain Kuppel; Josep Peñuelas; Luca Belelli Marchesini; Peter D. Blanken; Nina Buchmann; Jiquan Chen; Nicolas Delpierre; Ankur R. Desai; et al. (Global Ecology and Biogeography, 2019)
Aim The mechanisms of plant trait adaptation and acclimation are still poorly understood and, consequently, lack a consistent representation in terrestrial biosphere models (TBMs). Despite the increasing availability of geo‐referenced trait observations, current databases are still insufficient to cover all vegetation types and environmental conditions. In parallel, the growing number of continuous eddy‐covariance observations of energy and CO 2 fluxes has enabled modellers to optimize TBMs with these data. Past attempts to optimize TBM parameters mostly focused on model performance, overlooking the ecological properties of ecosystems. The aim of this study was to assess the ecological consistency of optimized trait‐related parameters while improving the model performances for gross primary productivity (GPP) at sites. Location Worldwide. Time period 1992–2012. Major taxa studied Trees and C 3 grasses. Methods We optimized parameters of the ORCHIDEE model against 371 site‐years of GPP estimates from the FLUXNET network, and we looked at global covariation among parameters and with climate. Results The optimized parameter values were shown to be consistent with leaf‐scale traits, in particular, with well‐known trade‐offs observed at the leaf level, echoing the leaf economic spectrum theory. Results showed a marked sensitivity of trait‐related parameters to local bioclimatic variables and reproduced the observed relationships between traits and climate. Main conclusions Our approach validates some biological processes implemented in the model and enables us to study ecological properties of vegetation at the canopy level, in addition to some traits that are difficult to observe experimentally. This study stresses the need for: (a) implementing explicit trade‐offs and acclimation processes in TBMs; (b) improving the representation of processes to avoid model‐specific parameterization; and (c) performing systematic measurements of traits at FLUXNET sites in order to gather information on plant ecophysiology and plant diversity, together with micro‐meteorological conditions.

Global wheat production with 1.5 and 2.0°C above pre‐industrial warming - Bing Liu; Pierre Martre; Frank Ewert; John R. Porter; Andy J. Challinor; Christoph Müller; Alex C. Ruane; Katharina Waha; Peter J. Thorburn; Pramod K. Aggarwal; Mukhtar Ahmed; Juraj Balkovič; et al. (Global Change Biology, 2019)
Efforts to limit global warming to below 2°C in relation to the pre‐industrial level are under way, in accordance with the 2015 Paris Agreement. However, most impact research on agriculture to date has focused on impacts of warming >2°C on mean crop yields, and many previous studies did not focus sufficiently on extreme events and yield interannual variability. Here, with the latest climate scenarios from the Half a degree Additional warming, Prognosis and Projected Impacts (HAPPI) project, we evaluated the impacts of the 2015 Paris Agreement range of global warming (1.5 and 2.0°C warming above the pre‐industrial period) on global wheat production and local yield variability. A multi‐crop and multi‐climate model ensemble over a global network of sites developed by the Agricultural Model Intercomparison and Improvement Project (AgMIP) for Wheat was used to represent major rainfed and irrigated wheat cropping systems. Results show that projected global wheat production will change by −2.3% to 7.0% under the 1.5°C scenario and −2.4% to 10.5% under the 2.0°C scenario, compared to a baseline of 1980–2010, when considering changes in local temperature, rainfall, and global atmospheric CO 2 concentration, but no changes in management or wheat cultivars. The projected impact on wheat production varies spatially; a larger increase is projected for temperate high rainfall regions than for moderate hot low rainfall and irrigated regions. Grain yields in warmer regions are more likely to be reduced than in cooler regions. Despite mostly positive impacts on global average grain yields, the frequency of extremely low yields (bottom 5 percentile of baseline distribution) and yield inter‐annual variability will increase under both warming scenarios for some of the hot growing locations, including locations from the second largest global wheat producer—India, which supplies more than 14% of global wheat. The projected global impact of warming

Climate change impact and adaptation for wheat protein - Senthold Asseng; Pierre Martre; Andrea Maiorano; Reimund P. Rötter; Garry J. O’Leary; Glenn J. Fitzgerald; Christine Girousse; Rosella Motzo; Francesco Giunta; M. Ali Babar; Matthew P. Reynolds; Ahmed M. S. Kheir; et al. (Global Change Biology, 2019)
Wheat grain protein concentration is an important determinant of wheat quality for human nutrition that is often overlooked in efforts to improve crop production. We tested and applied a 32‐multi‐model ensemble to simulate global wheat yield and quality in a changing climate. Potential benefits of elevated atmospheric CO 2 concentration by 2050 on global wheat grain and protein yield are likely to be negated by impacts from rising temperature and changes in rainfall, but with considerable disparities between regions. Grain and protein yields are expected to be lower and more variable in most low‐rainfall regions, with nitrogen availability limiting growth stimulus from elevated CO 2 . Introducing genotypes adapted to warmer temperatures (and also considering changes in CO 2 and rainfall) could boost global wheat yield by 7% and protein yield by 2%, but grain protein concentration would be reduced by −1.1 percentage points, representing a relative change of −8.6%. Climate change adaptations that benefit grain yield are not always positive for grain quality, putting additional pressure on global wheat production.

Multimodel ensembles improve predictions of crop–environment–management interactions - Daniel Wallach; Pierre Martre; Bing Liu; Senthold Asseng; Frank Ewert; Peter J. Thorburn; Martin van Ittersum; Pramod K. Aggarwal; Mukhtar Ahmed; Bruno Basso; Christian Biernath; Davide Cammarano; et al. (Global Change Biology, 2018)
A recent innovation in assessment of climate change impact on agricultural production has been to use crop multimodel ensembles ( MME s). These studies usually find large variability between individual models but that the ensemble mean (e‐mean) and median (e‐median) often seem to predict quite well. However, few studies have specifically been concerned with the predictive quality of those ensemble predictors. We ask what is the predictive quality of e‐mean and e‐median, and how does that depend on the ensemble characteristics. Our empirical results are based on five MME studies applied to wheat, using different data sets but the same 25 crop models. We show that the ensemble predictors have quite high skill and are better than most and sometimes all individual models for most groups of environments and most response variables. Mean squared error of e‐mean decreases monotonically with the size of the ensemble if models are added at random, but has a minimum at usually 2–6 models if best‐fit models are added first. Our theoretical results describe the ensemble using four parameters: average bias, model effect variance, environment effect variance, and interaction variance. We show analytically that mean squared error of prediction ( MSEP ) of e‐mean will always be smaller than MSEP averaged over models and will be less than MSEP of the best model if squared bias is less than the interaction variance. If models are added to the ensemble at random, MSEP of e‐mean will decrease as the inverse of ensemble size, with a minimum equal to squared bias plus interaction variance. This minimum value is not necessarily small, and so it is important to evaluate the predictive quality of e‐mean for each target population of environments. These results provide new information on the advantages of ensemble predictors, but also show their limitations.

High-resolution monitoring of marine protists based on an observation strategy integrating automated on-board filtration and molecular analyses - Katja Metfies; Friedhelm Schroeder; Johanna Hessel; Jochen Wollschläger; Sebastian Micheller; Christian Wolf; Estelle Kilias; Pim Sprong; Stefan Neuhaus; Stephan Frickenhaus; Wilhelm Petersen (Ocean Science, 2016)
Information on recent biomass distribution and biogeography of photosynthetic marine protists with adequate temporal and spatial resolution is urgently needed to better understand the consequences of environmental change for marine ecosystems. Here we introduce and review a molecular-based observation strategy for high-resolution assessment of these protists in space and time. It is the result of extensive technology developments, adaptations and evaluations which are documented in a number of different publications, and the results of the recently completed field testing which are introduced in this paper. The observation strategy is organized at four different levels. At level 1, samples are collected at high spatiotemporal resolution using the remotely controlled automated filtration system AUTOFIM. Resulting samples can either be preserved for later laboratory analyses, or directly subjected to molecular surveillance of key species aboard the ship via an automated biosensor system or quantitative polymerase chain reaction (level 2). Preserved samples are analyzed at the next observational levels in the laboratory (levels 3 and 4). At level 3 this involves molecular fingerprinting methods for a quick and reliable overview of differences in protist community composition. Finally, selected samples can be used to generate a detailed analysis of taxonomic protist composition via the latest next generation sequencing technology (NGS) at level 4. An overall integrated dataset of the results based on the different analyses provides comprehensive information on the diversity and biogeography of protists, including all related size classes. At the same time the cost of the observation is optimized with respect to analysis effort and time.

Reassessment of an Arabidopsis cell wall invertase inhibitor AtCIF1 reveals its role in seed germination and early seedling growth - Tao Su; Sebastian Wolf; Mei Han; Hongbo Zhao; Hongbin Wei; Steffen Greiner; Thomas Rausch (Plant Molecular Biology, 2016)

A Modeling and Simulation Framework for Adverse Events in Erlotinib-Treated Non-Small-Cell Lung Cancer Patients - Ahmed Abbas Suleiman; Sebastian Frechen; Matthias Scheffler; Thomas Zander; Lucia Nogova; Martin Kocher; Ulrich Jaehde; Jürgen Wolf; Uwe Fuhr (The AAPS Journal, 2015)

The Eugen Seibold coral mounds offshore western Morocco: oceanographic and bathymetric boundary conditions of a newly discovered cold-water coral province - Silke Glogowski; Wolf-Christian Dullo; Peter Feldens; Volker Liebetrau; Jonas von Reumont; Veit Hühnerbach; Sebastian Krastel; Russell B. Wynn; Sascha Flögel (Geo-Marine Letters, 2015)

Multimodel ensembles of wheat growth: many models are better than one - Pierre Martre; Daniel Wallach; Senthold Asseng; Frank Ewert; James W. Jones; Reimund P. Rötter; Kenneth J. Boote; Alex C. Ruane; Peter J. Thorburn; Davide Cammarano; Jerry L. Hatfield; Cynthia Rosenzweig; et al. (Global Change Biology, 2015)
Crop models of crop growth are increasingly used to quantify the impact of global changes due to climate or crop management. Therefore, accuracy of simulation results is a major concern. Studies with ensembles of crop models can give valuable information about model accuracy and uncertainty, but such studies are difficult to organize and have only recently begun. We report on the largest ensemble study to date, of 27 wheat models tested in four contrasting locations for their accuracy in simulating multiple crop growth and yield variables. The relative error averaged over models was 24–38% for the different end‐of‐season variables including grain yield ( GY ) and grain protein concentration ( GPC ). There was little relation between error of a model for GY or GPC and error for in‐season variables. Thus, most models did not arrive at accurate simulations of GY and GPC by accurately simulating preceding growth dynamics. Ensemble simulations, taking either the mean (e‐mean) or median (e‐median) of simulated values, gave better estimates than any individual model when all variables were considered. Compared to individual models, e‐median ranked first in simulating measured GY and third in GPC . The error of e‐mean and e‐median declined with an increasing number of ensemble members, with little decrease beyond 10 models. We conclude that multimodel ensembles can be used to create new estimators with improved accuracy and consistency in simulating growth dynamics. We argue that these results are applicable to other crop species, and hypothesize that they apply more generally to ecological system models.

Erratum to: New mouse models for metabolic bone diseases generated by genome-wide ENU mutagenesis - Sibylle Sabrautzki; Isabel Rubio-Aliaga; Wolfgang Hans; Helmut Fuchs; Birgit Rathkolb; Julia Calzada-Wack; Christian M. Cohrs; Matthias Klaften; Hartwig Seedorf; Sebastian Eck; Ana Benet-Pagès; Jack Favor; et al. (Mammalian Genome, 2014)

Report on the 42nd joint meeting of the DPG-working group Nematology and the working group “free living nematodes” - Matthias Daub; Ulrike Hakl; Beira Hailu Maressa; Heinz-Wilhelm Dehne; Johannes Hallmann; Sebastian Kiewnick; Caroline Eberlein; Holger Heuer; Jan H Moos; Hans M Paulsen; Andreas Westphal; Dieter Sturhan; et al. (Journal of Plant Diseases and Protection, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

External application of gametophyte-specific ZmPMEI1 induces pollen tube burst in maize - Mayada Woriedh; Sebastian Wolf; Mihaela L. Márton; Axel Hinze; Manfred Gahrtz; Dirk Becker; Thomas Dresselhaus (Plant Reproduction, 2013)

A sink‐limited growth model improves biomass estimation along boreal and alpine tree lines - Sebastian Leuzinger; Corina Manusch; Harald Bugmann; Annett Wolf (Global Ecology and Biogeography, 2013)
Aim Despite increasing evidence for plant growth often being limited by sink (meristem) activity rather than source (photosynthesis) activity, all currently available dynamic global vegetation models ( DGVMs ) simulate plant growth via source‐limited processes. For a given climatic region, this may lead to an overestimation of carbon stock per unit surface area, particularly if a model fails to correctly predict forest cover. Our aim is to improve the L und– P otsdam– J ena (LPJ) DGVM by replacing the source‐limited ( SoL ) tree growth algorithm by a sink‐limited ( SiL ) one. Location Our analysis focuses on the cold tree line at high latitudes and altitudes. We study two altitudinal transects in the S wiss A lps and the northern tree line. Methods We limit annual net primary productivity of the LPJ DGVM by an algorithm based on the annual sum of growing degree‐days ( GDD ), assuming that maximum plant growth is reached asymptotically with increasing GDD . Results Comparing simulation results with observational data, we show that the locations of both the northern and the alpine tree line are estimated more accurately when using a SiL algorithm than when using the commonly employed SoL algorithm. Also, simulated carbon stocks decrease in a more realistic manner towards the tree line when the SiL algorithm is used. This has far‐reaching implications for estimating and projecting present and future carbon stocks in temperature‐limited ecosystems. Main conclusions In the range of 60–80° N over E urope and A sia, carbon stored in vegetation is estimated to be c . 50% higher in the LPJ standard version ( LPJ ‐ SoL ) compared with LPJ ‐ SiL , resulting in a global difference in estimated biomass of 25 Pg ( c . 5% of the global terrestrial standing biomass). Similarly, the simulated elevation of the upper tree line in the E uropean A lps differs by c . 400 m between the two model versions, thus implying an additional overestimation of carbon stored in mountain forests around the world.

A plant's perspective of extremes: terrestrial plant responses to changing climatic variability - Christopher P.O. Reyer; Sebastian Leuzinger; Anja Rammig; Annett Wolf; Ruud P. Bartholomeus; Antonello Bonfante; Francesca de Lorenzi; Marie Dury; Philipp Gloning; Renée Abou Jaoudé; Tamir Klein; Thomas M. Kuster; et al. (Global Change Biology, 2013)
We review observational, experimental, and model results on how plants respond to extreme climatic conditions induced by changing climatic variability. Distinguishing between impacts of changing mean climatic conditions and changing climatic variability on terrestrial ecosystems is generally underrated in current studies. The goals of our review are thus (1) to identify plant processes that are vulnerable to changes in the variability of climatic variables rather than to changes in their mean, and (2) to depict/evaluate available study designs to quantify responses of plants to changing climatic variability. We find that phenology is largely affected by changing mean climate but also that impacts of climatic variability are much less studied, although potentially damaging. We note that plant water relations seem to be very vulnerable to extremes driven by changes in temperature and precipitation and that heatwaves and flooding have stronger impacts on physiological processes than changing mean climate. Moreover, interacting phenological and physiological processes are likely to further complicate plant responses to changing climatic variability. Phenological and physiological processes and their interactions culminate in even more sophisticated responses to changing mean climate and climatic variability at the species and community level. Generally, observational studies are well suited to study plant responses to changing mean climate, but less suitable to gain a mechanistic understanding of plant responses to climatic variability. Experiments seem best suited to simulate extreme events. In models, temporal resolution and model structure are crucial to capture plant responses to changing climatic variability. We highlight that a combination of experimental, observational, and/or modeling studies have the potential to overcome important caveats of the respective individual approaches.

New mouse models for metabolic bone diseases generated by genome-wide ENU mutagenesis - Sibylle Sabrautzki; Isabel Rubio-Aliaga; Wolfgang Hans; Helmut Fuchs; Birgit Rathkolb; Julia Calzada-Wack; Christian M. Cohrs; Matthias Klaften; Hartwig Seedorf; Sebastian Eck; Ana Benet-Pagès; Jack Favor; et al. (Mammalian Genome, 2012)

Growth control by cell wall pectins - Sebastian Wolf; Steffen Greiner (Protoplasma, 2012)

Nitrogen deposition increases susceptibility to drought - experimental evidence with the perennial grass Molinia caerulea (L.) Moench - Uta Friedrich; Goddert von Oheimb; Wolf-Ulrich Kriebitzsch; Kristina Schleßelmann; Malte Sebastian Weber; Werner Härdtle (Plant and Soil, 2012)

Afforestation of Tropical Pasture Only Marginally Affects Ecosystem-Scale Evapotranspiration - Sebastian Wolf; Werner Eugster; Sonja Majorek; Nina Buchmann (Ecosystems, 2011)

Carbon sequestration potential of tropical pasture compared with afforestation in Panama - SEBASTIAN WOLF; WERNER EUGSTER; CATHERINE POTVIN; BENJAMIN L. TURNER; NINA BUCHMANN (Global Change Biology, 2011)
Tropical forest ecosystems play an important role in regulating the global climate, yet deforestation and land‐use change mean that the tropical carbon sink is increasingly influenced by agroecosystems and pastures. Despite this, it is not yet fully understood how carbon cycling in the tropics responds to land‐use change, particularly for pasture and afforestation. Thus, the objectives of our study were: (1) to elucidate the environmental controls and the impact of management on gross primary production (GPP), total ecosystem respiration (TER) and net ecosystem CO 2 exchange (NEE); (2) to estimate the carbon sequestration potential of tropical pasture compared with afforestation; and (3) to compare eddy covariance‐derived carbon budgets with biomass and soil inventory data. We performed comparative measurements of NEE in a tropical C 4 pasture and an adjacent afforestation with native tree species in Sardinilla (Panama) from 2007 to 2009. Pronounced seasonal variation in GPP, TER and NEE were closely related to radiation, soil moisture, and C 3 vs. C 4 plant physiology. The shallow rooting depth of grasses compared with trees resulted in a higher sensitivity of the pasture ecosystem to water limitation and seasonal drought. During 2008, substantial amounts of carbon were sequestered by the afforestation (–442 g C m –2 , negative values denote ecosystem carbon uptake), which was in agreement with biometric observations (–450 g C m –2 ). In contrast, the pasture ecosystem was a strong carbon source in 2008 and 2009 (261 g C m –2 ), associated with seasonal drought and overgrazing. In addition, soil carbon isotope data indicated rapid carbon turnover after conversion from C 4 pasture to C 3 afforestation. Our results clearly show the potential for considerable carbon sequestration of tropical afforestation and highlight the risk of carbon losses from pasture ecosystems in a seasonal tropical climate.

Lake‐wide distributions of temperature, phytoplankton, zooplankton, and fish in the pelagic zone of a large lake - Karsten Rinke; Andrea M. R. Huber; Sebastian Kempke; Magdalena Eder; Thomas Wolf; Wolfgang N. Probst; Karl-Otto Rothhaupta (Limnology and Oceanography, 2009)
We studied three‐dimensional distribution patterns of temperature, phyto‐ and zooplankton, and fish in the large, prealpine Lake Constance during spring 2007. A strong westerly wind induced an intense eastward displacement of epilimnetic water and upwelling of hypolimnetic water in the western part of the lake. This led to the formation of an internal front separating cold, hypolimnetic water depleted of chlorophyll in the western part from epilimnetic, warm water with high chlorophyll concentrations in the eastern part. Hydroacoustic detection of zooplankton (by Acoustic Doppler Current Profiler) and juvenile fish (by echosounding) revealed both to be passively transported by the wind. Consequently, zooplankton and fish showed comparable horizontal distributions as temperature and chlorophyll. During periods of low wind velocities ( −1 ), water temperature was more evenly distributed, whereas phytoplankton distribution was still heterogeneous, probably because of local differences in resource supply. The relative influence of biotic factors for the distribution of organisms increased when external forcing was low. At periods with weak wind forcing, phytoplankton typically showed highest concentrations in the metalimnion, where zooplankton also aggregated in thin layers. In conclusion, we found spatial distributions of temperature and organisms to be strongly controlled by wind forcing when wind velocities were sufficiently high, whereas the importance of internal biotic factors for distribution of organisms increased when wind velocities were less strong. Abiotic factors appeared to act over relatively large spatial scales and affected distributions within the entire ecosystem, whereas biotic factors affected distributions of algae, zooplankton, and fish on a more local scale.

Conjunct rotation: Codman’s paradox revisited - Sebastian I. Wolf; Laetitia Fradet; Oliver Rettig (Medical & Biological Engineering & Computing, 2009)

Spatial synchronization of an insole pressure distribution system with a 3D motion analysis system for center of pressure measurements - Laetitia Fradet; Johannes Siegel; Marieke Dahl; Merkur Alimusaj; Sebastian I. Wolf (Medical & Biological Engineering & Computing, 2009)

Seeweite Bodensee-Messkampagne 2007 als Test für BodenseeOnline - Magdalena Eder; Karsten Rinke; Sebastian Kempke; Andrea Huber; Thomas Wolf (WASSERWIRTSCHAFT, 2008)

Development of new microsatellite loci and evaluation of loci from other pinniped species for the Galápagos sea lion (Zalophus californianus wollebaeki) - Jochen B.W. Wolf; Diethard Tautz; Adalgisa Caccone; Sebastian Steinfartz (Conservation Genetics, 2006)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)